Handbook of occupational safety and health - Koradecka, D. [ (Danuta)] (Human factors and ergonomics, 2010)
Occupational safety and health - safe work in a safe environment. The challenge, of course, is how to make this happen and make it happen economically. This book provides a range of methods along with specific criteria for assessing hazard and exposure in the workplace environment